ANALISIS KESUKSESAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN (STUDI KASUS DI HOTEL INDIGO SEMINYAK BALI) - Gusi Putu Lestara Permana; Ni Putu Yuli Wulandari (Jurnal Ilmiah Akuntansi & Bisnis, 2020)
This study aims to determine the successful implementation of "opera" management information system at Hotel Indigo Seminyak Bali is to analyze whether there is a positive influence on the quality of information, quality system, and user satisfaction on the impact of the organization on the Hotel. Indigo Seminyak Bali. The population of this study is all employees of Hotel Indigo Seminyak Bali who use the system "opera" itself. This research uses quantitative data analysis and literature study. In this study using questionnaires distributed on 52 respondents with predetermined criteria. The results of this study were tested by validity test, reliability test, classical assumption test which includes normality test, heteroskedastisiitas test, multicolinearity test and linear different test and hypothesis test which include F test, t test The results obtained after the test is the quality of Information has a positive and significant impact on the organizational impact of 0.216 which means the better the quality of information, the better the impact on the organization, quality system has a positive and significant impact on employee organization impact of 0.317 means the better quality system, the better the impact on the organization, and user satisfaction has a positive and significant impact on employee organization Impact of 0.469 which means the better of the consumer attitudes, also the better the impact on the organization. Keywords:        Information Quality, System Quality, User Satisfaction, Organizational Impact